Duloxetine in the treatment of binge eating disorder with depressive disorders: A placebo-controlled trial - Guerdjikova, Anna I.; McElroy, Susan L.; Winstanley, Erin L.; Nelson, Eric B.; Mori, Nicole; McCoy, Jessica; Keck Jr, Paul E.; Hudson, James I. (The International journal of eating disorders, 2012)
Objective: This study evaluated duloxetine in the treatment of binge eating disorder (BED) with comorbid current depressive disorders. Method: In this 12‐week, double‐blind, placebo‐controlled trial, 40 patients with Diagnostic and Statistical Manual of Mental Disorders‐IV‐TR BED and a comorbid current depressive disorder received duloxetine (N = 20) or placebo (N = 20). The primary outcome measure was weekly binge eating day frequency. Results: In the primary analysis, duloxetine (mean 78.7 mg/day) was superior to placebo in reducing weekly frequency of binge eating days (p = .04), binge eating episodes (p = .02), weight (p = .04), and Clinical Global Impression‐Severity of Illness ratings for binge eating (p = .02) and depressive disorders (p = .01). Changes in body mass index and measures of eating pathology, depression, and anxiety did not differ between the two groups. Discussion: Duloxetine may be effective for reducing binge eating, weight, and global severity of illness in BED with a comorbid current depressive disorder, but this finding needs confirmation in larger, placebo‐controlled trials. © 2011 by Wiley Periodicals, Inc. (Int J Eat Disord 2012)